Developing gender transformative approaches to strengthen women’s rights in Kyrgyzstan. Foundational gender analysis - Ibraeva, Gulnara; Ablezova, Mehrigiul; Danshina, Anastasiia; Elias, Marlene (2024)
The project paired with the Global Initiative, the Access to Markets Project (ATMP) (2016-2024), aims to raise incomes and enhance economic growth in pastoralist communities. Its development objective is to improve access and integration of smallholder livestock farmers into remunerative markets for their products, leading to improved and equitable returns.